PINK1 Deficiency Ameliorates Cisplatin-Induced Acute Kidney Injury in Rats - Zhou, Li; Zhang, Ling; Zhang, Yu; Yu, Xuan; Sun, Xiuping; Zhu, Tao; Li, Xianglei; Liang, Wei; Han, Yunlin; Qin, Chuan (Frontiers in Physiology, 2019)
Mitophagy plays a key role in cleaning damaged and depolarized mitochondria to maintain cellular homeostasis and viability. Although it was originally found in neurodegenerative diseases, mitophagy is reported to play an important role in acute kidney injury. PINK1 and Parkin are key molecules in mitophagy pathway. Here, we used PINK1 knockout rats to examine the role of PINK1/Parkin-mediated mitophagy in cisplatin nephrotoxicity. After cisplatin treatment, PINK1 knockout rats showed lower plasma creatinine and less tubular damage when compared with wild-type rats. Meanwhile, mitophagy indicated by autophagosome formation and LC3B-II accumulation was also attenuated in PINK1 knockout rats. Renal expression of PINK1 and Parkin were down-regulated while BNIP3L was up-regulated by cisplatin treatment, indicating a major role of BNIP3/BNIP3L pathway in cisplatin-induced mitophagy. Transmission electron microscopy showed that PINK1 deficiency inhibited cisplatin-induced mitochondrial fragmentation indicating an involvement of mitochondrial fusion and fission. Renal expression of mitochondrial dynamics related proteins including Fis1, Drp1, Mfn1, Mfn2, and Opa1 were checked by real-time PCR and western blots. The results showed PINK1 deficiency distinctly prevented cisplatin-induced up-regulation of DRP1. Finally, PINK1 deficiency alleviated cisplatin-induced tubular apoptosis indicated by TUNEL assay as well as the expression of caspase3 and cleaved caspase3. Together, these results suggested PINK1 deficiency ameliorated cisplatin-induced acute kidney injury in rats, possibly via inhibiting DRP1-mediated mitochondrial fission and excessive mitophagy.